Variasi Zooplankton di Kolam Budi Daya Ikan Air Tawar di Kabupaten Minahasa Provinsi Sulawesi Utara - Rumaseb, Tince (Universitas Sam Ratulangi, 2014)
Zooplankton variation in fresh water fish pond on North Minahasa District of North Sulawesi Province was done in five different areas.Â The goal is to evaluate the variation and the abundance of zooplankton.Â The result is copepod is the first rank in abundance (50% on April and 51% on August), followed by cladoceran (32% on April and 33% on August) and finally, rotifer (18% on April and 16% on August). Keywords : zooplankton, fish pond, fresh water, variation, abundance